Less invasive cardiac anesthesia: an ultra-fast-track procedure avoiding thoracic epidural analgesia - Brucek, Peter Jan; Straka, Zbynek; Vanek, Tomas; Jares, Martin (The heart surgery forum, 2003)
BACKGROUND AND OBJECTIVE: A new "less invasive" technique avoiding thoracic epidural analgesia has be en tested for suitability as a routine procedure for cardiac anesthesia. Early postoperative extubation is an important step in this fasttrack procedure. MATERIALS AND METHODS: Consecutive patients (n = 547; age, 35-82 years; mean age, 64 year s; male to female ratio, 3.5) underwent general anesthesia with ultra-short-acting opiates and then underwent coronary surgery (n = 465), valve surgery (n = 38), or combined and other procedures (n = 44) a r;. In 51.4% cases, coronary artery bypass grafting was performed off pump. The percentage of patients extubated within 10 minutes after skin closure was the primary end point. In addition, we attempted to identify the limiting factors of the procedure tested. RESULTS AND DISCUSSION: Of the 547 patients, 499 (91%) were extubated within 10 minutes after skin closure. Early extubation failed in 48 (9%) of the patients. The mortality rate was 1.5%. One (0.2%) of the patients needed early reintubation because of pneumothorax. Postoperative myocardial ischemia was recorded in 10 (1.8%) of the patients. Ninetysix (17.5%) of the patients were treated pharmacologically for newly developed atrial fibrillation. None of the patients needed hemodialysis. Transient neurological disorders were recorded in 10 (1.8%) of the patients. The early extubation failure group showed statistically significantly higher rates of preoperative lung dysfunction, use of extracorporeal circulation, administration of inotropic drugs in the operating room, and statistically significantly longer duration of surgery. CONCLUSION: Early extubation proved suitable as a routine procedure for the vast majority of patients. With a good postoperative analgetic protocol, there is no need for thoracic epidural analgesia. Such avoidance of thoracic epidural analgesia is a further step in minimizing invasiveness in cardiac surgery.
Keywords: dospělí; Analgesia, Epidural; Female; Ventilator Weaning; Feasibility Studies; epidurální analgezie; Cardiac Surgical Procedures; Adult; ženské pohlaví; Time Factors; časové faktory; Anesthesia, General; lidé; kardiochirurgické výkony; celková anestezie; Aged, 80 and over; srdeční chlopně; Reoperation; Middle Aged; reoperace; studie proveditelnosti; odpojení od ventilátoru; Male; Aged; koronární bypass; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Heart Valves; Coronary Artery Bypass; Humans